Search for a dimuon resonance in the ϒ mass region; Journal of High Energy Physics; № 9 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen